Guerra, Exilio, Diaspora.Aproximaciones Literariase Historicas - Marin Villora, Maria Trinidad; August-Zarębska, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
In the autobiographic trilogy The forging of a rebel (La forja de un rebelde) Arturo Barea (1897–1957) describes his very personal experiences from the times of his childhood until the end of the Spanish Civil War in 1936. In each volume the author depicts a different moment of his personal history, determined by the social and political circumstances of that time.In the third volume of his autobiography Barea presents his personal and pessimistic vision of the Spanish Civil War of 1936. Having witnessed many atrocities committed by both sides of the conflict, the writer, who had been the enthusiastic supporter of the socialist cause, turns into a very disillusioned man, deeply worried about the future of his homeland. Moreover, because of the permanent contact with destruction and death, the writer suffers from nervous breakdowns. Disappointed and concerned about his health, Barea decides to give literary shape to his personal experiences. Writing the autobiography helps him recover from the illness and overcome the traumatic experience of the Spanish Civil War. Encue_
Keywords: emigracja - w literaturze; imigracja - w literaturze; literatura hiszpańska - tematy, motywy; Hiszpania - wojna domowa; Hiszpania - literatura; Hiszpania - wojna